Pengembangan Metode Pembelajaran Sains Berbasis Wisata Edu-Herbal di Desa Bukit Bamba dalam Meningkatkan Minat Belajar Siswa di Masa Pandemi Covid-19 - Liberti Natalia Hia; Yusnani Dewi Sus (Neolectura, 2020)
Central Kalimantan has a myriad of medicinal or herbal plants; these plants are beneficial for life. So that it gets the title of a live laboratory, that is the reason the ancestors were familiar with using natural ingredients as medicine, for example, ant nest plants, rapids, earthen pegs, sungkai leaves, etc. The current generation rarely knows and likes herbal plants, even though herbal medicines are known to be safer than synthetic chemical drugs, for that the scope of education needs to introduce the types of herbal plants and their properties. The choice of chemical studies tends to be in the classroom and the laboratory there is no option to study in nature which is a living laboratory or real laboratory lab, through direct observation or local tours of herbal edu This natural material can be used as medicine. Bukit Bamba village, Kahayan Tengah sub-district, Pulang Pisau district, is famous for its tourism area which is rich in herbal sources and designated as a sustainable forest by the Ministry of Environment and Forestry for the conservation of forest areas including medicinal plants. This village for tourism takes strict health protocols into account. Qualitative analysis using descriptions of the main data collection using observations, interviews or document review, using inductive data analysis, based on the results of the research of students who he took on a local tour experienced an increase in interest in learning..